Impact of Coupling Strength on Reaching Network Consensus - Yang, Chun-lin; Suh, C. Steve; Karkoub, Mansour (Journal of Applied Nonlinear Dynamics, 2026)
The coupling strength of a real-world network is studied to gain insight into the dynamics of state consensus. Real-world networks such as AUV fleets and bird flocks are highly nonlinear on the node level while environmental disturbance and communication error an aggravate the dynamic state of nonlinearity and non-stationarity on the network level. It is therefore necessary that a comprehensive consensus control methodology be developed so as to help hold the network together as a whole in an energy efficient way. However, the significance of coupling strength in affecting state consensus is usually ignored in the literature. This article investigates the issue with a focus on the impact of coupling strength.